Knowledge of Diabetic Complications in a Diabetic Population - Hoque, Mirza Azizul; Islam, Md Sirajul; Khan, Md Abdul Maleque; Ahasan, HAM Nazmul (Journal of Medicine, 2009)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> This cross-sectional, questionnaire based descriptive study was carried out to evaluate the individual knowledge of diabetic complications in the diabetic patients and also to find the association of knowledge towards educational status and other socio-demographic profiles. A total 184 patients were included in this study. In this study, we found 91 subjects (48.9%) knew that heart disease was the most important diabetic complication, if blood glucose level wasn't controlled properly followed by cerebrovascular disease 27(14.7%), renal disease 24(13%) and eye diseases 9(4.9%). Unfortunately, awareness about frequency of diabetic foot disease, peripheral neurological problems, occurrence of sudden death were found in only 1(0.5%) cases. Awarness about other complications (miscellaneous) was 12(6.5%) and 8(4.3%) didn't know any of the above mentioned complications. Each subject was also asked whether they were apprehensive about the dreaded diabetic complications or not. Statistical difference wasn't observed in any of the parameter (i.e., individual education, an area of residence, monthly income, occupations, family history of individual) when compared with the degree of apprehension. None of the parameters was statistically significant. Further expansion of diabetic education programs like using mass media and involving national curriculum of education can improve self-regulatory awareness of diabetic complications which may reduce the morbidity and mortality of diabetic patients. Key words: diabetic complication, apprehension. doi: 10.3329/jom.v10i2.2821 J MEDICINE 2009; 10 : 90-93